Dialysis utilization in the Toronto region from 1981 to 1992. Toronto Region Dialysis Committee. - Mendelssohn, D C (1994)
OBJECTIVE: To analyse trends in the demand for and supply of dialysis in the Toronto region and to determine whether planned dialysis expansion will be sufficient to provide for the projected growth of the dialysis population. DESIGN: Descriptive analysis of data reported to the Toronto Region Dialysis Registry between 1981 and 1992, compared with provincial and national equivalents. SETTING: All secondary and tertiary care dialysis programs in the Toronto region participating in the registry. PATIENTS: All 504 existing patients enrolled in dialysis programs in 1981 and all 3794 new patients entering programs from 1982 to 1992. Patients with acute renal failure were excluded. MAIN OUTCOME MEASURES: Demand for dialysis: dialysis population at year end, age distribution, crude mortality rate and transplant rate. Supply of resources: distribution of modality (hemodialysis or peritoneal dialysis), number of patients treated per hemodialysis station, number of hemodialysis stations per million population and hemodialysis utilization index (actual/budgeted treatments). RESULTS: During the study period the number of dialysis patients in the Toronto region went from 504 to 1422, for an increase of 182.1%. The average rate of growth was 9.8% per year. Of the total increment of 918 patients from 1981 to 1992, 390 (42.5%) were 65 years of age or more; none the less, the average annual crude mortality rate remained relatively constant, at 13.8% to 17.3%. The transplantation rate declined from a peak of 20.2% in 1982 to 7.8% in 1992. During the study period the Toronto region had much higher numbers of dialysis patients, and hemodialysis patients, per hemodialysis station than the rest of Ontario or Canada. The region's hemodialysis utilization index was 101% in 1991 and 102% in 1992; the index in individual hospitals varied from 98% to 124% (85% was considered optimal). CONCLUSIONS: The growth of the dialysis population in the Toronto region has caused a critical shortage of resources. This trend can be attributed mainly to a decrease in the transplantation rate and an increase in the number of elderly patients entering dialysis programs, combined with insufficient funding for expansion of facilities. Continuation of this trend would be expected to limit universal access to this expensive, but life-sustaining therapy.